Earnings Management dalam Penawaran Saham Perdana di Bursa Efek Jakarta - Tatang Ari Gumanti (The Indonesian Journal of Accounting Research, 2013)
This paper examines whether issuers of initial public offerings (IPO) select accounting methods by making income-increasing discretionary accruals in the periods prior to the offering. Issuers are well motivated to increase the reported earnings given two potential reasons. First, the absence of market price information prior to the offering has made it difficult for parties involved in the new issue market, i.e., underwriter, issuers, and potential investors, to price the offering rationally. Second, this condition, coupled with the widely accepted argument that earnings performance has been the target of stock valuation for most investors in the capital market, may provide opportunity and motivation for the issuers the affect the firm’s reported earnings.Tests were conducted on 39 IPO firms that went public for the periods 1995-1997 at the Jakarta Stock Exchange. The method used to examine earnings management follows the one developed by Friedlan (1994) as has been tested in the US’ IPOs. Friedlan uses total accruals as proxy for discretionary accruals and modifies the model adjusted to account for the data limitation and specific characteristics of an IPO setting.The results show that accruals management is found in the period of two years prior to the offering. The hypotheses that the median discretionary accruals and median change of total accruals, operating earnings, and cash flow from operations are greater than zero can not be rejected. Interestingly, accruals management does not really exist in the period of one year prior to the offering. In other words, there is a weak evidence for earnings management one year prior to public offer.